PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DAN PENDAPATAN ASLI DAERAH LAINNYA YANG SAH TERHADAP BELANJA DAERAH DI KABUPATEN DAN KOTA PROVINSI JAWA TENGAH - LMS Kristiyanti; Mustika Ndaru Cahyani; Wikan Budi Utami (ITB AAS INDONESIA, 2022)
This study aims (1) to find out how much influence local taxes, regional levies and other legitimate local revenue have on regional expenditures in the province of Central Java simultaneously. (2) To find out how big the influence of local taxes on regional spending in the province of Central Java. (3) To find out how big the influence of regional levies on regional expenditures in the province of Central Java. (4) To find out how much influence other legitimate regional original income has on regional expenditures in the province of Central Java. (5) To determine the magnitude of the influence of regional taxes, regional levies, and other legitimate regional original revenues on regional expenditures. The hypothesis test in this study uses the f statistic test, the t statistic test, the coefficient of determination test. The population in this study includes all districts and cities in the province of Central Java. The samples used were 27 regencies/cities, so the total sample for 2 years was 54 regencies and cities. The results of this study indicate that: (1) local taxes (X1) have a significant effect on regional spending (Y). (2) regional retribution (X2) has no significant effect on regional expenditure (Y). (3) other legitimate regional original income (X3) has a significant effect on regional expenditure (Y). (4) regional taxes, regional levies, other legitimate regional original revenues on regional expenditures have simultaneous effects.